The Role of Education through Animation Media on Knowledge and Attitudes Towards Balanced Nutrition in Elementary School Students - Juli Malinda; Iman Jalandri; Shelly Festilia Agusanty (MEDICA (International Medical Scientific Journal), 2023)
Balanced nutrition is essential for a child's growth and development, enhancing their ability to learn and providing positive impacts for their future development. Knowledge and attitudes towards nutrition play a crucial role in determining the level of public health. Various nutritional and health problems can arise due to a lack of knowledge and attitudes regarding balanced nutrition. The aim of this study is to determine the effect of nutrition education through animation video media on knowledge and attitudes towards balanced nutrition among fifth-grade students at SDN 01 Teluk Batang, Kayong Utara. The research method used was a pre-experimental design with a "one group pretest-posttest" design. The sampling method used in this study involved the entire population, which consisted of 30 fifth-grade students. The results of the study indicated that there was an increase in knowledge and attitudes towards balanced nutrition before and after providing nutrition education through animation video media to elementary school students at SDN 01 Teluk Batang, Kayong Utara. In conclusion, there was a significant difference in knowledge about balanced nutrition before and after the nutrition education through animation video media. Furthermore, attitudes towards balanced nutrition also showed a difference before and after the nutrition education through animation video media among the elementary school students at SDN 01 Teluk Batang, Kayong Utara.